Chaetomugilin J Enhances Apoptosis in Human Ovarian Cancer A2780 Cells Induced by Cisplatin Through Inhibiting Pink1/Parkin Mediated Mitophagy - Hu, Xiaoqing (Onco Targets Ther, 2020)
PURPOSE: The chemoresistance and toxicity of traditional chemotherapeutic drugs have become obstacles to their antitumor effects in ovarian cancers. Therefore, it is particularly important to develop new anticancer drugs to increase target sensitivity and reduce the toxicity of chemotherapy drugs. As key organelles, the endoplasmic reticulum and mitochondria play important role in chemoresistance. Cells become resistant to drugs by maintaining the homeostasis of the endoplasmic reticulum and mitochondria. Chaetomugilin J, a metabolite isolated from Polygonatum sibiricum, belongs to the Chaetomium family and exhibits potent cytotoxicity. In this study, we aimed to explore the mechanistic link between apoptosis and endoplasmic reticulum stress, mitophagy and mitochondrial dysfunction induced by chaetomugilin J combined with cisplatin in the ovarian cancer cell line A2780. METHODS: Chaetomugilin J was identified by chemical methods. Cell viability was measured by an MTT assay. The apoptosis, mitochondrial membrane potential, and intracellular reactive oxygen species (ROS) were examined by flow cytometry. Mitochondrial ROS was measured by a fluorescence microscope with MitoSox staining. Further, the related proteins and overexpression of parkin were detected by Western blot. RESULTS: Chaetomugilin J combined with low-dose cisplatin decreased cell viability and increased apoptosis in A2780 cells. In addition, intracellular ROS and mitochondrial ROS were increased, while the mitochondrial membrane potential was reduced. The expressions of grp78 and chop were decreased after treatment by chaetomugilin J combined with low-dose cisplatin. Overexpression of parkin attenuated chaetomugilin J combined with cisplatin-induced apoptosis. CONCLUSION: Chaetomugilin J combined with cisplatin inhibited pink1/parkin mediated mitophagy increased mitochondrial dysfunction in the A2780 cells and enhanced apoptosis induced by cisplatin in the ovarian cancer cell line A2780. But this process was not related to endoplasmic reticulum apoptotic pathway.